Nickel-Based Electrocatalysts for Hydrogen Evolution:A Comprehensive Review of Recent Progress (Development Engineering Conferences Center Articles Database, 2025)
The escalating severity of global climate challenges, coupled with the progressive depletion of fossil fuel reserves, has rendered energy transition an urgent global imperative. Electrochemical water splitting powered by renewable energy sources represents a promising and sustainable strategy for hydrogen production. In this context, the development of efficient electrocatalysts for the HER (Hydrogen Evolution Reaction) is crucial. Among various candidates, nickel-based electrocatalysts have attracted significant attention due to their natural abundance, excellent corrosion resistance, high electrical conductivity, and outstanding electrocatalytic activity across a wide range of electrolytes. Platinum-based materials are considered standard electrocatalysts for the HER. These materials exhibit nearly zero overpotential and high stability as hydrogen producers. However, the high cost and the scarcity of noble metal-based materials hinder their practical use in large-scale applications. This review article focuses on the recent advances in Ni-based electrocatalysts for HER.